Pengembangan Literasi Sekolah melalui Pelatihan Menulis Cerita - Yusniarsi Primasari; Hesty Puspita Sari; Adin Fauzi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
Abstract. Referring to the result of Indonesia National Assessment Programme in 2017, the literacy (reading and writing skills) of elementary school students were still low, that is, only 46.83%. This condition needs to be improved, and one of the ways to enhance it is by implementing Gerakan Literasi Sekolah (GLS)/School Literacy Movement. This community service aims to improve the students’ writing skill as en effort to implement the GLS. This community service was conducted in the form of training of story writing. The training was implemented at one of the Islamic Elementary School in Blitar, East Java. The participants of the training included the students of grade 4, 5, and 6, totalling 52 students. The training was conducted by applying flipped classroom. The material is given to the students in the form of video that they should learn online, and subsequently they were given face-to-face writing guidance in the classroom. The results showed that the students were able to create a story about their experiences during the pandemic. The analysis of students’ writing revealed that the students’ abilities in composing a text was good. These abilities include developing ideas and using proper words and sentence structure. However, most of the students still encountered difficulties in using mechanics of writing, such as capitalization and punctuation. This needs to be followed up by intensifying writing activity at school, and generating other trainings to enhance the students’ writing skill.